2019
DOI: 10.1109/access.2018.2883802
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Heuristic Coevolution of Machine Assignment and Job Sequencing Rules for Multi-Objective Dynamic Flexible Job Shop Scheduling

Abstract: Nowadays, real-time scheduling is one of the key issues in cyber-physical system. In real production, dispatching rules are frequently used to react to disruptions. However, the man-made rules have strong problem relevance, and the quality of results depends on the problem itself. The motivation of this paper is to generate effective scheduling policies (SPs) through off-line learning and to implement the evolved SPs online for fast application. Thus, the dynamic scheduling effectiveness can be achieved, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…The dynamic production scheduling (DPS) [12]- [20] means that the planned scheduling solution can be adjusted in real time to minimize the impact on the performance of production system when disruption events occur randomly. Furthermore, the adjusted scheduling solutions should be consistent, efficient and robust to complete production tasks against disruption events.…”
Section: Imentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic production scheduling (DPS) [12]- [20] means that the planned scheduling solution can be adjusted in real time to minimize the impact on the performance of production system when disruption events occur randomly. Furthermore, the adjusted scheduling solutions should be consistent, efficient and robust to complete production tasks against disruption events.…”
Section: Imentioning
confidence: 99%
“…This paper here proposes a weighted sum of properties (WSP) dispatching rule, as shown in Equation (17). On the basis of hyper-heuristic concept [15], [16], [20], the WSP dispatching rule needs the IoMT-based FMMAL actively perceive the production conditions and dynamically search the priority weights to generate the priorities according to the optimization objectives. Three considered process properties of products in MC are the assembly time, due time and assembly power, which correspond to three optimization objectives of minimizing the C max , TET and TEC.…”
Section: A Decision Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Wang [19] employed the constraint programming and mixed-integer linear programming to formulate the flexible assembly job-shop scheduling problem in a dynamic manufacturing environment, and developed several dispatching rules with machine feedback mechanism. Zhou et al [20] proposed three types of hyper-heuristic methods for coevolution of the machine assignment rules and job sequencing rules to solve the multiobjective dynamic flexible job shop scheduling problem, and found that the heuristics discovered by the evolved scheduling policies are more useful and competitive. The above studies are very inspiring, but they fail to design the hyper-heuristics on the basis of product properties, including the assembly time, due time and assembly power.…”
Section: Related Workmentioning
confidence: 99%
“…Ahmadi et al [16] used NSGA-II and non-dominated ranking genetic algorithm (NRGA) to optimize the makespan and stability under the disturbance of machine breakdown. Zhou et al [17] presented a cooperative coevolution genetic programming with two sub-populations to generate scheduling policies. Zhang et al [18] utilized a genetic algorithm combined with enhanced local search to solve the energy-efficiency job shop scheduling problems.…”
Section: Literature Reviewmentioning
confidence: 99%